SMALL AND MEDIUM ENTERPRISES (SMES) IN NAMANGAN’S GREEN ECONOMY (KIUT Publication, 2025)
This article explores the critical role of Small and Medium Enterprises (SMEs) in advancing the green economy in Namangan, Uzbekistan. It analyzes the current landscape, characteristics, and contributions of SMEs within key sectors such as agriculture, manufacturing, and renewable energy. The paper assesses the policy and institutional frameworks that support green SME development and identifies key challenges including limited access to green finance, technical capacity gaps, regulatory hurdles, and market constraints. Through case studies of pioneering green SMEs, the study highlights best practices and innovative approaches. Finally, it proposes strategic recommendations to enhance the growth, sustainability, and inclusivity of green SMEs, positioning them as vital drivers of Namangan’s transition to a low-carbon, resource-efficient, and socially equitable economy.